Simulation and experiment of heat and mass transfer in a proton exchange membrane electrolysis cell. (7th August 2020) - Zhang, Zhuqian; Xing, Xiaohui
Abstract: A full-scale, two-phase, single-channel model of proton exchange membrane electrolysis cell is established. The electrochemical model and the thermal model are coupled to explore the mass transfer of the channel, catalytic layer and diffusion layer, and the heat transfer of the entire electrolysis cell. Two different calculation models are compared, and it is found that the calculation results of the model with bipolar plates are closer to the actual values. Simultaneously, effective water and thermal management strategies are proposed: The temperature of the electrolysis cell can be reduced effectively by supplying water to the cathode side. The Counter-flow mode has a lower temperature than the Co-flow mode, but the temperature gradient in the Counter-flow mode is greater. Reducing the channel depth and increasing the channel width can improve the water transmission in the electrolysis cell and reduce the temperature of the electrolysis cell, but a larger channel width will increase the electrical loss. Therefore, the selection of appropriate channel size is of great significance to the long-term stable operation of the electrolysis cell. Highlights: Three dimensional and two-phase model are developed for a PEM electrolysis. The fluid in the electrolytic cell is a homogeneous flow. Electrochemical model and thermal model are considered simultaneously. The structure of the flow field significantly affects the heat and mass transfer.